Elaboración y caracterización de una película biodegradable proveniente del mucílago de nopal, almidón de papa, glicerol y ácido acético para la sustitución de plásticos convencionales. (2025)
This study presents the development of a biodegradable biofilm from cactus mucilage, potato starch, glycerin and acetic acid, as a sustainable alternative to conventional plastic. Cactus mucilage, known for its gelling properties and its abundance in the semi-arid region of Espinal, Tolima, was extracted by ethanol precipitation, a method that optimizes both the purity and performance of the material. Different formulations were evaluated, selecting a mixture of 1.5 g of mucilage powder, 3 g of potato starch, 1.57 g of acetic acid and 1.89 g of glycerin as the most efficient. Mechanical tests revealed that the biofilm has a tensile strength considerably higher than low-density polyethylene (LDPE), with a maximum stress between 70 and 150 N/mm2, compared to 10-30 N/mm2 for LDPE. However, biofilm shows a lower deformation capacity, with a maximum displacement of 4-9 mm compared to more than 10 mm for LDPE, and an elastic modulus of 0.2-0.6 N/mm2 compared to 200-300 N/mm2 for LDPE. These results indicate that biofilm is better suited for applications that prioritize resistance to high loads over flexibility.